Significance of granulomatous inflammation in usual interstitial pneumonia - Tomic, Rade; Kim, Hyun J; Perlman, David M; Bors, Melinda; Allen, Tadashi; Ritter, Jon; Dincer, H Erhan; Bhargava, Maneesh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Sarcoidosis is a systemic granulomatous disease of unclear etiology with characteristic pulmonary lesions. We describe 2 unique cases of sarcoidosis where after approximately 20 years of clinical quiescence, patients developed interstitial opacities on chest CT scan and an increase in shortness of breath. With lack of therapeutic response to a course of prednisone, both patients underwent a surgical lung biopsy that revealed a pattern consistent with Usual Interstitial Pneumonia (UIP) with honeycombing and fibroblastic foci. Postoperatively, the course of the disease was consistent with what would be expected in Idiopathic Pulmonary Fibrosis. Ultimately the disease progressed with one patient needed lung transplantation and the other requiring high-flow oxygen supplementation. In conclusion, we present two patients in whom a diagnosis of sarcoidosis preceded the diagnosis of UIP by 20 years or more. The subsequent course of disease in both patients was consistent with Idiopathic Pulmonary Fibrosis (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 160-166)